Single-cell analysis of peripheral blood and pleural effusion reveals functional diversity of γδ T cells in tuberculosis infection - Feng, Yanjun; Chen, Yu; Zhang, Wanying; Shen, Xinghua; Yan, Jinyu; Yao, Lin; Zhang, Lijuan; Niu, Yayan; Zhang, Jianping; Tang, Peijun; Ling, Chunhua (Frontiers in Immunology, 2025)
IntroductionTuberculosis is a contagious airborne disease caused by the Mycobacterium tuberculosis infection. γδ T cells are closely associated with TB infection; however, the specific role of γδ T cells in the immune response to TB remains unclear, as does the differentiation and mechanism of γδ T cell subsets in TB patients.MethodsWe analyzed the characteristics of γδ T subsets in the peripheral blood (Peripheral Blood Mononuclear Cells,PBMC) and pleural effusions (Tuberculous pleural effusion,TPE) and pleural effusions of TB patients using single-cell sequencing to explore the distribution and characteristics of different γδ T subpopulations.ResultsSeven γδ Tcell subpopulations were identified. The highest percentage of effector γδ2 cell cluster (C1) was found in PBMCs from TPE patients, accounting for 36.1%, while the highest percentage of tissue-resident γδ2 cell cluster (C0) was found in PFMCs, reaching 70.5%. Through in-depth analysis, we identified a group of Vδ2 cells exhibiting strong effector function and high expression of FCGR3A.DiscussionTherefore, exploring the mechanism of interaction between Vδ2 cells and Mtb, as well as understanding host immune regulation during Mtb infection, can not only enhance the understanding of the immune mechanism underlying TB but also provide new theoretical ideas. This research may offer novel therapeutic targets for TB and innovative strategies for treatment and prevention.